Measuring communicative competence of future heads of educational institutions in the process of a pedagogical experiment - Chebotarova, I. O. (Problems of Engineer-Pedagogical Education, 2018)
Under the conditions of modernizing the system of higher education, the issues of measuring the level of the formation of communicative competence of future principals of educational institutions in the system of Master's degree programs are acquiring considerable weight. The author has developed and suggested a system for measuring the communicative competence of future administrators of educational institutions within the framework of Master's degree programs, basing on the qualimetric approach. The article presents the results of measuring the communicative competence of future heads of educational institutions in the process of conducting a pedagogical experiment that took place between 2014 and 2016 i within the framework of Master's degree program in the specialty 073 Management «Management of educational institutions». The entry and final control of the main factors was made in the experimental and control groups. The results of the experimental work proved the effectiveness of the technology developed by the author and showed a high level of the formation of communicative competence among Master's graduates in the experimental groups.